DEVELOPING ADVANCED FACIAL RECOGNITION SOFTWARE USING VIDEO CAMERAS: TECHNIQUES AND APPLICATIONS - Hamiyev A.T.; Kholiyorov Kh.A. (PEDAGOGS, 2024)
This article explores the development of advanced facial recognition software using video cameras. The focus is on the image processing techniques and biometric technologies employed to enhance facial recognition accuracy. Key methodologies include feature extraction, encoding, and image segmentation, which are essential for identifying and analyzing facial features. The thesis also discusses the creation and implementation of robust algorithms for real-time detection and recognition, emphasizing the software's practical applications in security systems. This comprehensive study highlights the potential of integrating facial recognition technology into various real-world scenarios, offering significant improvements in security and efficiency.